The experimental study of partial discharge of Malaysian based palm oil - Aziz, Muhamad Fikri (2012)
Insulation is one of the most important parts in a high voltage apparatus, while insulator is a material that resists the flow of the electric current. Most of the transformer used liquid insulating material where its function is to provide electrical insulation and also act as a coolant to prevent overheating of the transformer. Since years ago, petroleum-based mineral oil has been used as a coolant and insulation purpose because of its high electric field strength, low dielectric losses and good long-term performance. There are some reasons that push the search of environmental friendly insulating oils. Conventional transformer insulating materials are usually non-biodegradable. It can contaminate soil and water when serious spill take place. This may disturb the plantation and other lives. In future, this petroleum will be come to an end because it is a non-renewable source. Therefore, this project has been carried out to seek alternatives of vegetables oil that is more environmental friendly. Refined, bleached and deodorized palm oil (RBDPO) has been recognized to be the potential replacement for petroleum-based mineral oil. The main objective of this project is to execute experimental study effect of ageing time and electrical characteristic of Refined, Bleached and Deodorized Palm Oil (RBDPO) by using partial discharge method. Another objective of this project is to make a comparison on electrical properties between new insulating oil, RBDPO with petroleum-based mineral oil. The result indicates the prospect of RBDPO to be further processed to get better dielectric properties and meet all requirements to be used as liquid insulating material. This is because RBDPO has a potential to be a good liquid insulator because of its high breakdown voltage, low dissipation factor and low capacitance when different ageing time were applied